Perancangan Sistem Cetak ID Card Siswa Berbasis Web Menggunakan Metode Prototype Di MTS Arrahmaniyah - Kurnianto Putra, Ryu; Bayu Prasetyo Wibowo, Muhammad; Dhafa Putrautama, Muhammad; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Student identification is a crucial aspect of supporting various school activities. However, the process of creating student ID cards at MTs Arrahmaniyah is still performed manually, which is time-consuming and prone to errors. This research aims to design a web-based student ID card printing system using the prototype method. This method enables iterative development involving user feedback during the design process. The system includes features for managing student data, card design, and efficient card printing. Testing results indicate that the system improves efficiency and accuracy in ID card creation. It is expected that this system can be implemented to support effective school administration digitization.